(untitled) (مجلة الفاروق للعلوم, 2026)
The oil and gas sector is facing growing pressure to meet the needs of operations, the environment and regulatory requirements, and stakeholder expectations. Such tensions are especially strong in nascent petroleum economies such as Libya, where the existing infrastructure, insufficient institutional capacity and underdeveloped environmental management systems create a structure which hinders sustainable performance. A mediation model between green education and sustainable operation practices is developed and theoretically justified based on the systematic literature review of the existing literature. The synthesis was done using the results of a systematic literature review according to PRISMA 2020 guidelines, which resulted in 57 studies that were retrieved from Scopus, Web of Science, and EBSCO databases (2010-2026). Based on the Ability–Motivation–Opportunity (AMO) theory, Theory of Planned Behavior (TPB), and Institutional Theory, the paper proposes a multi-level theoretical framework and offers four testable hypotheses regarding the direct and indirect linkages between the three constructs. The review shows that: (1) green education is not a stand-alone training activity, but rather a systemic organizational learning capability; (2) environmental awareness is the key cognitive mediation mechanism that transforms learning inputs into sustainable learning behavioral outputs; and (3) current models do not adequately consider the specificities of a developing petroleum economy. Five new research gaps that have not been previously addressed in the literature are identified, and an original Workforce Sustainability Capability Framework (WSCF) is proposed as a theoretical contribution and practical approach. This paper contributes to the literature in three ways: (1) it conceptualizes green education as an operationally embedded construct of workforce capability with specified dimensions and mechanisms; (2) it views environmental awareness as a theoretically specified three-dimensional cognitive mediator; and (3) it proposes the first integrated conceptual model of green education, environmental awareness, and sustainable operational practices in the Libyan petroleum context which can serve as a basis for future empirical studies and practical workforce development policy.